Effect of Sowing Dates on the Yield of Sunflower (Bangladesh Agronomy Journal, 2015)
The experiment was carried out at Agronomy Research field of Bangladesh Agricultural Research Institute (BARI), Joydebpur, Gazipur and Regional Agricultural Research Station, Hathazari, Chittagong to find out optimum sowing date of sunflower during rabi season 2012-13. The sunflower var. BARI Surjomukhi-2 was used. Five sowing dates; 10 November, 20 November, 30 November, 10 December and 20 December were tested. It was revealed that yield and yield attributes of sunflower were significantly influenced by sowing dates. The maximum plant height (172.13 cm), head diameter (18.33), weight of seed / per head (66 g), 1000- seed weight (68 g) and yield (2.5 t ha?1) were obtained from 20 November sowing. The lowest yield (1.83 t ha?1) was obtained from 20 December sowing. The 20 November sowing received the higher duration for maturity (127 days), first flowering (57 days) and seed formation (20 days) while 20 December sowing showed shorter duration for maturity, first flowering and seed formation of 119, 54 and 14 days respectively. It was concluded that the 20 November sowing would be the optimum time of sowing for achieving maximum yield of sunflower.Bangladesh Agron. J. 2015, 18(1): 1-5